LEGAL PROTECTION OF FLOWER HAWKERS THROUGH THE PROVISION OF LEGALITY AND BRAND RIGHTS (CASE STUDY IN TONGGONDOA VILLAGE PALIBELO DISTRICT OF BIMA REGENCY) - Aman Ma’arij; Gufran (Awang Long Law Review, 2022)
This research is a legal research that examines the legal protection of flower snack producers in Tonggondoa Village, Palibelo District, Bima Regency, precisely in RT 03 RW 02 Dusun Doro To'i. The purpose of this research is to provide legal protection in the form of granting legality to flower snacks producers and branding the products of flower snacks in Tonggondoa Village referring to the provisions of the Minister of Trade Regulation Number 77/M-DAG/PER/12/2013 concerning the Issuance of Trading Business Permits and Simultaneous Company Registration Certificates for Trading Companies and Law Number 11 of 2020 concerning Job Creation and Law Number 20 of 2016 concerning Marks and Geographical Indications to improve the welfare of the people in Tonggondoa Village. The method used in this study is an empirical legal research method, with several approaches, including: a statutory approach and a concept approach. The results showed that the flower snack producers in Tonggondoa Village from the legal aspect had not received legality as a business group and the flower snacks produced had not received legal protection in the form of labeling and branding that could increase the selling value of flower snacks. Originality: this research is very important considering that no previous research has been conducted on this matter, considering that the flower snack producers in Tonggondoa Village have been around for a long time but there has not been any effort and attention to the legality of flower snacks producers and legal protection efforts for flower snacks production.